Analisis finansial peremajaan perkebunan sawit rakyat di Kabupaten Muaro Jambi - Murdy, Saad; Nainggolan, Saidin; Napitupulu, Dompak (Jurnal Paradigma Ekonomika, 2021)
This study aims to (1) determine the feasibility of smallholder oil palm plantations assessed from a financial perspective using investment criteria, (2) determine the sensitivity of smallholder oil palm plantations to changes in input and output prices. This research was conducted in Muaro Jambi Regency. The method of analysis used an analysis of investment criteria consisting of NPV, IRR, BCR, PBP, and BEP. The data used were primary data obtained through interviews using questionnaires. Samples were taken by snowball sampling of 40 small independent smallholders of Muaro Jambi Regency. The results showed that smallholder oil palm plantations, conventional rejuvenation, and underplanting rejuvenation were feasible to be cultivated. The results of the sensitivity analysis on the increase in the price of production factors by 15% and the selling price of FFB is considered constant, and the selling price of FFB has decreased by 15% and the price of production factors is fixed, both types of oil palm plantation rejuvenation are still feasible to carry out. Changes in FFB prices are more sensitive to changes in the value of investment criteria than changes in the price of production factors. Â